Suspected menopause nutraceutical-induced eosinophilic ascites: a rare clinical presentation - Gemma Vicens-Novell; Alejandro Alonso-Galera; Rosa Muñoz-Cano; Joaquín Sáez-Peñataro (BMJ Case Reports, 2026)
A middle-aged woman presented with a 2-month history of ascites without associated symptoms. She reported taking no regular medication, except for a menopause supplement for the preceding 4 months. Initial blood investigation revealed marked peripheral eosinophilia (49%) but was otherwise unremarkable. Analysis of the ascitic fluid demonstrated a predominance of eosinophils (90%) with no evidence of malignancy. Abdominal ultrasonography identified liver lesions; however, malignancy was excluded by CT. Gastroscopy findings were normal and biopsies showed no malignant features. Tumour markers were within normal limits, except for an elevated CA-125 level. Autoimmune and infectious causes were excluded and no other underlying cause for the ascites was identified. Following discontinuation of the dietary supplement, both the ascites and eosinophilia resolved within a month without specific treatment. The temporal relationship and subsequent clinical improvement after withdrawal highlight the supplement as a possible contributing factor to eosinophilic ascites and hypereosinophilia.